Modelo estructural para liderazgo y emprendimiento de mujeres indígenas Yukpas (2021)
The objective of this work is to design a structural model that identifies explanatory variables of leadership and entrepreneurship in the Yukpa community. The research follows an ethnographic method and mixed approach: qualitative using elements of factorial and correlational design, based on structural equation modeling (SEM) and quantitative in that instruments such as interview, observation and survey are implemented in a sample of 174 members of the Yukpa community in the municipality of Cúcuta-Colombia. The results allow identifying emerging categories in Yukpa women such as discipline, compassion, solidarity, example, for leadership and participative planning, context, production, organization, marketing, training in entrepreneurship; likewise, solidarity, use of ancestral practices, economic social factors, product, affect consumer behavior. It is concluded that from the logarithmic logit model with base two, the representation in entrepreneurship influenced by the behavior of the leader of the community and the consumer of products in the Yukpa tribe's offer is identified.